High frequency of clinical conditions commonly associated with mitochondrial disorders in schizophrenia. Issue 5 (24th October 2020) - Alonso, Yolanda; Valiente-Pallejà, Alba; Verge, Begoña; Vilella, Elisabet; Martorell, Lourdes
Abstract: Objective: It has been hypothesised that neuropsychiatric symptoms, including psychosis, can be the result of a milder brain bioenergetic defect produced by mitochondrial dysfunction; however, mitochondrial dysfunction can be present in other organs or systems. The aim of the study was to investigate whether clinical conditions associated with mitochondrial disorders (CAMDs) were frequently present in schizophrenia. Methods: A previously used questionnaire regarding the CAMDs was administered to patients and controls in a direct interview with a trained psychiatrist. The frequencies of CAMDs in 164 patients with schizophrenia were compared to those in 156 age- and sex-matched controls. Results: Severe fatigue, seizures, constipation and diabetes were significantly more frequent in patients with schizophrenia than in control subjects and apparently not related to pharmacological treatment. Conclusion: The results of the present study suggest that multi-systemic mitochondrial dysfunction may be an underlying mechanism involved in schizophrenia.